MONSEHE RITUAL PERFORMED BY CULAMBU ETHNIC PEOPLE IN NORTH KONAWE REGENCY, SOUTHEAST SULAWESI - Mustaman, Mustaman Mustaman; Kumbara, A.A. Ngurah Anom; Wirawan, A.A. Bagus Wirawan; Arsana, I Gusti Ketut Gde (E-Journal of Cultural Studies; Vol 8 No 1 (2015): Volume 8, Number 1, Februari 2015, 2015)
The existence of the local culture in the globalization era is a highly interesting phenomenon to explore. The close relationship between human beings and the culture proves that human beings cannot live without culture; how primitive they are, as exemplified by the life of the Culambacu ethnic people. Based on such an assumption, the monsehe ritual becomes an interesting thing to explore. The problems of the present study can be formulated as follows: how the monsehe ritual performed by the Culambacu ethnic people is like; what ideologies contribute to the monsehe ritual; and what meaning it contains. The data in the present study were collected through observation, interview, library research, and documentation. The theory of functional structure, the theory of semiotics, and the theory of hegemony were used to analyze the problems of the study. The result of the study shows that, first , the monsehe ritual is performed to ward off misfortune ( mosehe inia ) and to settle conflict and adultery, and to treat sick people. In addition, it is also performed as part of the death ceremony. Second , the monsehe ritual contains cosmological ideology and religious ideology. Third , the totality of the mosehe ritual which is performed by the Culambacu ethnic people is accumulated in the form of symbols which are rich in meanings such as religious meaning, harmonious meaning, educational meaning, identity meaning, social control meaning, and solidarity meaning.
Keywords: monsehe ritual, ideology, animism.